Gastrointestinal Tolerability of Ibuprofen Administered in Two Pharmaceutical Formulations - Zuin, Massimo; Podda, Mauro; Selmi, Carlo; Giorgini, Alessia; Zermiani, Paola; Mandelli, Giovanna; Cristina Sacchetta, Anna; Candiani, Carlo (Arzneimittelforschung, 2000)
Ibuprofen (CAS 15687-27-1) is a nonsteroidal antiinflammatory drug endowed with analgesic, antiinflammatory and antipyretic activity. The main side effect of ibuprofen and nonsteroidal antiinflammatory agents is addressed to disturbances of the gastrointestinal tract, like gastric pyrosis, gastric and intestinal damage.A pharmaceutical formulation of ibuprofen in fast melting tablets consisting in gastroprotected microgranules to be ingested without concomitant water intake (Cibalginadue® Fast, hereinafter referred to as test) was compared in this trial with a formulation of ibuprofen in tablets (reference) on 18 healthy volunteers in terms of gastrointestinal and general tolerability. Both the formulations are present on the market. The two formulations were administered according to a two-period, two-formulation, two-sequence, cross-over design in repeated dose regimen to steady state with wash-out. The dose was 400 mg (2 strengths) b.i.d. over 7 days. Before, during and after each study period general tolerability was carefully checked from blood/urine biochemical parameters, adverse events experienced and vital signs. The target parameters were the gastric permeability to sucrose and the intestinal permeability to lactulose and mannitol, which were administered orally and assayed in the urine excreted during a 6-h period. Urinary excretion > 0.15 % of sucrose and > 0.04 of the lactulose to mannitol ratio are considered expression of increased gastric and intestinal permeability, respectively. Three volunteers treated with the reference showed an increased gastric permeability > 0.15 %. Neither other gastric nor intestinal increased permeability was detected. Occult blood in faeces was negative in all the cases.The incidence of adverse effects experienced was higher with the reference (9 volunteers) than with the test (5 volunteers). In details gastric pyrosis was experienced by six volunteers treated with the reference and only by two volunteers treated with the test. The whole tolerability was better with the test formulation than with the reference, even if these differences did not reach any statistically significant degree. The better tolerability of the test was attributed to its gastroprotection.
Keywords: Anti-inflammatories, non-steroidal; CAS 15687-27-1; Cibalginadue® Fast; Gastric and intestinal permeability; Ibuprofen, gastrointestinal tolerability, volunteers